Self-Adjuvanting Bacterial Vectors Expressing Pre-Erythrocytic Antigens Induce Sterile Protection Against Malaria - Bergmann-Leitner, Elke; Hosie, Heather; Whittington, Jessica; DeRiso, Elizabeth; Ranallo, Ryan; Alefantis, Timothy; Savranskaya, Tatyana; Grewal, Paul; Ockenhouse, Christian; Venkatesan, Malabi; DelVecchio, Vito; Angov, Evelina (Frontiers in Immunology, 2013)
Genetically inactivated, Gram-negative bacteria that express malaria vaccine candidates represent a promising novel self-adjuvanting vaccine approach. Antigens expressed on particulate bacterial carriers not only target directly to antigen-presenting cells but also provide a strong danger signal thus circumventing the requirement for potent extraneous adjuvants. E. coli expressing malarial antigens resulted in the induction of either Th1 or Th2 biased responses that were dependent on both antigen and sub-cellular localization. Some of these constructs induced higher quality humoral responses compared to recombinant protein and most importantly they were able to induce sterile protection against sporozoite challenge in a murine model of malaria. In light of these encouraging results, two major Plasmodium falciparum pre-erythrocytic malaria vaccine targets, the Cell-Traversal protein for Ookinetes and Sporozoites (CelTOS) fused to the Maltose-binding protein in the periplasmic space and the Circumsporozoite Protein (CSP) fused to the Outer membrane (OM) protein A in the OM were expressed in a clinically relevant, attenuated Shigella strain (Shigella flexneri 2a). This type of live-attenuated vector has previously undergone clinical investigations as a vaccine against shigellosis. Using this novel delivery platform for malaria, we find that vaccination with the whole-organism represents an effective vaccination alternative that induces protective efficacy against sporozoite challenge. Shigella GeMI-Vax expressing malaria targets warrant further evaluation to determine their full potential as a dual disease, multivalent, self-adjuvanting vaccine system, against both shigellosis, and malaria.